GCM Objective 13: In Search of Synergies with the UN Human Rights Regime to Foster the Rule of Law in the Area of Immigration Detention - Izabella Majcher (Laws, 2022)
Reflecting the focus of this Special Issue on “Rule of Law and Human Mobility in the Age of the Global Compacts,” this article contributes to the discussion on the threats to the rule of law posed by immigration detention through the lens of the Global Compact for Safe, Orderly and Regular Migration (GCM). In GCM’s Objective 13, states committed to use immigration detention only as a measure of last resort, work towards alternatives and draw from eight sets of actions to realise this commitment. Given the attention the GCM attracts, its nonbinding character and the voluntary nature of its review can be used by states as justification for their inadequate implementation of binding human rights obligations and insufficient reporting on implementation to the supervising bodies. While acknowledging these challenges to the rule of law, this article explores the ways the GCM can actually foster the rule of law in the area of immigration detention. To strengthen the rule of law principles of legality, legal certainty, prohibition of arbitrariness, access to justice and the right to an effective remedy, Objective 13 needs to support a binding human rights regime by preventing arbitrary detention and its implementation at the domestic level. The article discusses the interplay between Objective 13 on the one hand, and, on the other, the International Covenant on Civil and Political Rights, International Convention on the Protection of the Rights of All Migrant Workers and Members of Their Families and Convention on the Rights of the Child at three levels—the detention provisions, the support provided to states for the implementation of these provisions and the monitoring of states’ implementation—and it proposes means to strengthen the synergies between the two frameworks.